Effect of Dietary Bacillus subtilis Supplementation on Lymphoid Organ Weights and Antibody Production Against the Newcastle Disease Vaccine in Broiler Chicks - Bashir A.H.; Abdelatif A.M.; Elkhair N.M. (Journal of Applied Veterinary Sciences)
This study investigated the impact of Bacillus subtilis supplementation on lymphoid organ weights and antibody production in response to the Newcastle Disease Vaccine (NDV) in Ross 308 chicks. A total of 120 one-day-old chicks were divided into four groups with three replicates of 10 birds each, receiving different concentrations of Bacillus subtilis (Bs): Control (Bs-0), 0.05% (Bs-0.05), 0.10% (Bs-0.1), and 0.15% (Bs-0.15) for six weeks. Newcastle disease, infectious bronchitis and Gumboro disease vaccines were administered in drinking water on days 3, 11 and 15 of age, respectively. Blood and serum samples were harvested on day 21 to assess antibody production against NDV and lymphoid organ weights on day 42. On day 21, the antibody titers against the NDV vaccine were significantly higher (P≤0.05) in all chick groups supplemented with Bacillus subtilis compared to the control; the highest titer was observed in the Bs-0.15 group. By day 42, the final body weight (FBW) was significantly (P≤0.01) higher in the supplemented group Bs-0.15 than in others. The supplemented group, Bs-0.05, showed a numerically higher FBW than Bs-0.1 and the control group. The absolute and relative weights of lymphoid organs (spleen, thymus and bursa of Fabricius) were significantly higher (P≤0.01) in the supplemented groups than in the control. The highest organ weights were recorded in chicks receiving the highest concentration of Bacillus subtilis (Bs-0.15). These findings demonstrate that dietary supplementation with Bacillus subtilis at 0.15% enhances BW and the immune response and organ development associated with immunity in chicks. This supplementation levelimproves immune system health, bolsters disease resistance, and inspires and motivates further exploration of its potential utility in poultry nutrition strategies.